Preparation method of ternary composite supercapacitor material

CN116959894BActive Publication Date: 2026-10-30XI'AN POLYTECHNIC UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310565877.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-18
Publication Date
2026-10-30
Estimated Expiration
2043-05-18

AI Technical Summary

Technical Problem

[0005]本发明的目的是提供一种三元复合超级电容器材料的制备方法,解决了现有技术中存在的聚苯胺实际比电容较低、循环稳定性差的问题

Benefits of technology

[0022]本发明的有益效果是,以2,4-TDA为模板分子,丙烯酸为功能单体,采用多扫循环伏安法在碳纳米管修饰的铅笔芯电极(MWCNT–PEC)表面制备出高比电容和荷电量的复合材料2,4-二氨基甲苯分子印迹聚合物/聚十二烷基苯磺酸/聚苯胺(2,4-TDA-MIP/PDBSA/PANI)。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116959894B_ABST
    Figure CN116959894B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a ternary composite supercapacitor material, and specifically comprises the following steps: step 1, preparing 2,4-TDA-MIP-MWCNT-PEC; step 2, preparing a molecular imprinting polymer / polydodecylbenzenesulfonic acid modified electrode; and step 3, preparing 2,4-TDA-MIP / PDBSA / PANI, namely the ternary composite supercapacitor material. The application solves the problems of low actual specific capacitance and poor cycle stability of polyaniline in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of composite material preparation technology, specifically relating to a method for preparing a ternary composite supercapacitor material. Background Technology

[0002] Polyaniline (PANI) is widely used in electrode materials due to its simple preparation method, inexpensive raw materials, and good conductivity after doping. PANI possesses a π-electron conjugated structure. During the charging and discharging process of the electrode material, charges are placed between the polymer molecular chains, allowing for rapid and reversible p-type or n-type doping and dedoping processes, i.e., the charging and discharging process. This affects the electron cloud distribution of the conjugated bonds in the polymer molecules, altering the charge state and causing protonation or deprotonation reactions, ultimately resulting in a Faraday pseudocapacitor on a macroscopic scale. Simultaneously, due to the π-π conjugated bond transfer effect, electrons in the polymer readily participate in the reaction, leading to a specific capacitance of conductive polymer electrode materials that can generally reach more than twice that of double-layer supercapacitor materials, with a maximum theoretical specific capacitance as high as 1000 F / g. However, the doping / dedoping reactions cause continuous expansion and contraction of the PANI volume, resulting in poor cycle stability and a relatively low actual specific capacitance. Therefore, the introduction of other materials is necessary to overcome the limitations of PANI in practical applications.

[0003] Molecularly imprinted polymers (MIPs) are porous materials. The imprinted pores give them both external and internal surface areas, increasing their specific surface area. This increased specific surface area significantly improves the specific capacitance of polyaniline (PANI). Therefore, the imprinted pores of MIPs can be used in the synthesis of PANI. 2,4-Diaminotoluene (2,4-TDA), also known as toluene diamine, is a widely used intermediate in the preparation of organic chemicals and is an important raw material for toluene diisocyanate (TDI), one of the two important raw materials for the preparation of polyurethane (PU). Incorporating 2,4-diaminotoluene (2,4-TDA) molecularly imprinted polymers into the electrochemical synthesis of polyaniline increases the charge capacity of PANI and enhances its specific capacitance.

[0004] Dodecylbenzenesulfonic acid (DSBA) not only functions as a protic acid to donate hydrogen ions but also as a surfactant. In the synthesis of polyaniline, DSBA can improve the stability and conductivity of polyaniline, reduce the interfacial tension between polyaniline molecules, and increase the solubility of aniline, thereby increasing the polymerization rate of aniline. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing ternary composite supercapacitor materials, which solves the problems of low actual specific capacitance and poor cycle stability of polyaniline in the prior art.

[0006] The technical solution adopted in this invention is a method for preparing ternary composite supercapacitor materials, which is implemented according to the following steps:

[0007] Steps 1 and 2, Preparation of 4-TDA-MIP-MWCNT-PEC;

[0008] Step 2: Preparation of molecularly imprinted polymer / polydodecylbenzenesulfonic acid modified electrode;

[0009] Step 3, the preparation of 2,4-TDA-MIP / PDBSA / PANI, i.e., the ternary composite supercapacitor material.

[0010] The invention is further characterized in that,

[0011] Step 1 is implemented in the following steps:

[0012] Using multi-walled carbon nanotubes (MWCNT-PEC) as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum electrode as the counter electrode, the electrode was placed in a phosphate buffer solution (PBS) containing 2,4-diaminotoluene, acrylic acid, and potassium dihydrogen phosphate. After continuous cyclic scanning and washing, the MWCNT-PEC electrode, after completing the electrochemical reaction, was ultrasonically eluted in an ethanol-ammonia solution to obtain the 2,4-diaminotoluene molecularly imprinted polymer / multi-walled carbon nanotube modified pencil lead electrode 2,4-TDA-MIP / MWCNT-PEC.

[0013] In step 1, the effective electrode length of the multi-walled carbon nanotube (MWCNT-PEC) is 0.75-1.75 cm, and the concentration of 2,4-diaminotoluene is 1.0 × 10⁻⁶. -3 -5.0×10 -3 The concentration of acrylic acid is 5.0 × 10 mol / L. -3 -2.0×10 -2 mol / L, the pH of the PBS buffer is 5.91-7.17.

[0014] In step 1, the device continuously cycles 11 times at a scanning rate of 0.08V / s within a potential range of -1.2 to 1.2V. The device is cleaned several times with double-distilled water. The volume ratio of ethanol to ammonia in the ethanol-ammonia solution is 10:1 to 20:1. The ultrasonic elution time is 1 to 5 minutes.

[0015] Step 2 is implemented in the following steps:

[0016] A traditional three-electrode system was used, with the 2,4-diaminotoluene molecularly imprinted polymer / multi-walled carbon nanotube modified pencil lead electrode 2,4-TDA-MIP / MWCNT / PEC obtained in step 1 as the working electrode, a calomel electrode as the reference electrode, and a platinum electrode as the counter electrode. The electrode was continuously cyclically scanned in a 0.05-0.15 mol / L dodecylbenzenesulfonic acid (DBSA) solution, and dried to obtain the 2,4-diaminotoluene molecularly imprinted polymer / polydodecylbenzenesulfonic acid / multi-walled carbon nanotube modified pencil lead electrode 2,4-TDA-MIP / PDBSA / MWCNT / PEC.

[0017] In step 2, the scanning rate is 0.05-0.15V / s, the potential range is -0.2-0.6V, and the continuous cyclic scanning is performed for 6-14 cycles.

[0018] Step 3 is implemented in the following steps:

[0019] In a mixed solution of H2SO4 and C6H5N as the supporting electrolyte, using the 2,4-diaminotoluene molecularly imprinted polymer / polydodecylbenzenesulfonic acid / multi-walled carbon nanotube modified pencil lead electrode 2,4-TDA-MIP / PDBSA / MWCNT / PEC obtained in step 2 as the working electrode, 2,4-diaminotoluene molecularly imprinted polymer / polydodecylbenzenesulfonic acid / polyaniline 2,4-TDA-MIP / PDBSA / PANI can be obtained after continuous scanning.

[0020] In step 3, the concentration of H2SO4 in the mixed solution of H2SO4 and C6H5N is 0.2-0.8 mol / L, and the concentration of C6H5N is 0.05-0.3 mol / L.

[0021] In step 3, the scanning potential range is -0.2 to 1.85V, the scanning rate is 0.03 to 0.15V / s, and the scanning is continuous for 6 to 14 cycles.

[0022] The beneficial effect of this invention is that, using 2,4-TDA as a template molecule and acrylic acid as a functional monomer, a composite material with high specific capacitance and charge, 2,4-diaminotoluene molecularly imprinted polymer / polydodecylbenzenesulfonic acid / polyaniline (2,4-TDA-MIP / PDBSA / PANI), is prepared on the surface of a carbon nanotube-modified pencil lead electrode (MWCNT–PEC) using a multi-scan cyclic voltammetry method. Attached Figure Description

[0023] Figure 1(a) is a cyclic voltammetry curve of 2,4-TDA-MIP / PDBSA / PANI / PANI under different functional monomers of the present invention;

[0024] Figure 1(b) is a charge diagram of 2,4-TDA-MIP / PDBSA / PANI / PANI under different functional units of the present invention;

[0025] Figure 2(a) is a cyclic voltammetric curve of 2,4-TDA-MIP / PDBSA / PANI / PANI under different buffer solutions according to the present invention;

[0026] Figure 2(b) shows the charge plots of 2,4-TDA-MIP / PDBSA / PANI / PANI under different buffer solutions according to the present invention;

[0027] Figure 3(a) is a cyclic voltammetric curve of the buffer solution of the present invention at different pH values ​​of 2,4-TDA-MIP / PDBSA / PANI / PANI;

[0028] Figure 3(b) is a charge diagram of the buffer solution of the present invention at different pH values ​​of 2,4-TDA-MIP / PDBSA / PANI / PANI;

[0029] Figure 4(a) is a cyclic voltammetric curve of 2,4-TDA-MIP / PDBSA / PANI / PANI under different template molecule and functional monomer concentration ratios according to the present invention.

[0030] Figure 4(b) is a charge diagram of 2,4-TDA-MIP / PDBSA / PANI / PANI under different concentration ratios of template molecules and functional monomers in this invention;

[0031] Figure 5(a) is a cyclic voltammetry curve of 2,4-TDA-MIP / PDBSA / PANI / PANI under different scanning potentials according to the present invention;

[0032] Figure 5(b) is a charge diagram of 2,4-TDA-MIP / PDBSA / PANI / PANI under different scanning potentials according to the present invention;

[0033] Figure 6(a) is a cyclic voltammetry curve of 2,4-TDA-MIP / PDBSA / PANI / PANI under different scan cycles according to the present invention;

[0034] Figure 6(b) is a charge diagram of 2,4-TDA-MIP / PDBSA / PANI / PANI under different scan cycles of the present invention;

[0035] Figure 7(a) is a cyclic voltammetry curve of 2,4-TDA-MIP / PDBSA / PANI / PANI at different scan rates according to the present invention;

[0036] Figure 7(b) is a charge diagram of 2,4-TDA-MIP / PDBSA / PANI / PANI at different scan rates according to the present invention;

[0037] Figure 8(a) is a cyclic voltammetric curve of 2,4-TDA-MIP / PDBSA / PANI / PANI under different elution times according to the present invention;

[0038] Figure 8(b) is a charge diagram of 2,4-TDA-MIP / PDBSA / PANI / PANI under different elution times according to the present invention;

[0039] Figure 9 This is a comparison chart of the GCD curves of 2,4-TDA-MIP / DBSA / PANI and 2,4-TDA-MIP / PDBSA / PANI of the present invention;

[0040] Figure 10 This is a charge-discharge cycle data diagram of the 2,4TDA-PDBSA / PAN of the present invention. Detailed Implementation

[0041] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments.

[0042] This invention uses 2,4-TDA as a template molecule and acrylic acid as a functional monomer to prepare a composite material with high specific capacitance and charge on the surface of a carbon nanotube-modified pencil lead electrode (MWCNT–PEC) using multi-scan cyclic voltammetry: 2,4-diaminotoluene molecularly imprinted polymer / polydodecylbenzenesulfonic acid / polyaniline 2,4-TDA-MIP / PDBSA / PANI.

[0043] The preparation method of the ternary composite supercapacitor material of the present invention is specifically implemented according to the following steps:

[0044] Steps 1 and 2, preparation of 4-TDA-MIP-MWCNT-PEC;

[0045] Step 1 is implemented in the following steps:

[0046] Using multi-walled carbon nanotubes (MWCNT-PEC) as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum electrode as the counter electrode, the electrode was placed in a phosphate buffer solution (PBS) containing 2,4-diaminotoluene, acrylic acid, and potassium dihydrogen phosphate. After continuous cyclic scanning and washing, the MWCNT-PEC electrode, after completing the electrochemical reaction, was ultrasonically eluted in an ethanol-ammonia solution to obtain the 2,4-diaminotoluene molecularly imprinted polymer / multi-walled carbon nanotube modified pencil lead electrode 2,4-TDA-MIP / MWCNT-PEC.

[0047] In step 1, the effective electrode length of the multi-walled carbon nanotube (MWCNT-PEC) is 0.75-1.75 cm, and the concentration of 2,4-diaminotoluene is 1.0 × 10⁻⁶. -3 -5.0×10-3 The concentration of acrylic acid is 5.0 × 10 mol / L. -3 -2.0×10 -2 mol / L, the pH of the PBS buffer is 5.91-7.17.

[0048] In step 1, the device continuously cycles 11 times at a scanning rate of 0.08V / s within a potential range of -1.2 to 1.2V. The device is cleaned several times with double-distilled water. The volume ratio of ethanol to ammonia in the ethanol-ammonia solution is 10:1 to 20:1. The ultrasonic elution time is 1 to 5 minutes.

[0049] Step 2: Preparation of molecularly imprinted polymer / polydodecylbenzenesulfonic acid modified electrode;

[0050] Step 2 is implemented in the following steps:

[0051] A traditional three-electrode system was used, with the 2,4-diaminotoluene molecularly imprinted polymer / multi-walled carbon nanotube modified pencil lead electrode 2,4-TDA-MIP / MWCNT / PEC obtained in step 1 as the working electrode, a calomel electrode as the reference electrode, and a platinum electrode as the counter electrode. The electrode was continuously cyclically scanned in a 0.05-0.15 mol / L dodecylbenzenesulfonic acid (DBSA) solution, and dried to obtain the 2,4-diaminotoluene molecularly imprinted polymer / polydodecylbenzenesulfonic acid / multi-walled carbon nanotube modified pencil lead electrode 2,4-TDA-MIP / PDBSA / MWCNT / PEC.

[0052] In step 2, the scanning rate is 0.05-0.15V / s, the potential range is -0.2-0.6V, and the continuous cyclic scanning is performed for 6-14 cycles.

[0053] Step 3, the preparation of 2,4-TDA-MIP / PDBSA / PANI, i.e., the ternary composite supercapacitor material.

[0054] Step 3 is implemented in the following steps:

[0055] In a mixed solution of H2SO4 and C6H5N as the supporting electrolyte, using the 2,4-diaminotoluene molecularly imprinted polymer / polydodecylbenzenesulfonic acid / multi-walled carbon nanotube modified pencil lead electrode 2,4-TDA-MIP / PDBSA / MWCNT / PEC obtained in step 2 as the working electrode, 2,4-diaminotoluene molecularly imprinted polymer / polydodecylbenzenesulfonic acid / polyaniline 2,4-TDA-MIP / PDBSA / PANI can be obtained after continuous scanning.

[0056] In step 3, the concentration of H2SO4 in the mixed solution of H2SO4 and C6H5N is 0.2-0.8 mol / L, and the concentration of C6H5N is 0.05-0.3 mol / L.

[0057] In step 3, the scanning potential range is -0.2 to 1.85V, the scanning rate is 0.03 to 0.15V / s, and the scanning is continuous for 6 to 14 cycles.

[0058] Optimization of functional monomers for molecularly imprinted polymerization

[0059] The effects of three functional monomers—acrylic acid, methyl methacrylate, and acrylamide—on the charge of the 2,4-TDA-MIP / PDBSA / PANI / PANI composite material were investigated under the condition that the template molecule was 2,4-TDA. Figures 1(a) and 1(b) show the cyclic voltammetry curves and charge Q of the 2,4-TDA-MIP / PDBSA / PANI / PANI composite material under different functional monomers. As can be seen from Figures 1(a) and 1(b), the composite material exhibits the best performance when acrylic acid is used as the functional monomer. This is because there is an interaction between acrylic acid and 2,4-TDA, causing the acrylic acid to arrange itself in a certain order around 2,4-TDA. The ability of the vacancies in 2,4-TDA-MIP to recombine with the polymer is also improved, thus maximizing the charge and achieving the best electrochemical performance of the composite material.

[0060] During the polymerization of imprinted polymers, the binding of functional monomers and template molecules in solution is significantly affected by the type and pH of the buffer solution. At 1.0 × 10⁻⁶ pH... -3 2,4-Diaminotoluene mol / L, 4.0 × 10 -2 The effects of four different buffer solutions on the charge of the composite material were investigated in mol / L acrylic acid. The results are shown in Figures 2(a) and 2(b). The composite material with potassium dihydrogen phosphate-borax solution, disodium hydrogen phosphate-citric acid solution, sodium hydroxide-potassium dihydrogen phosphate solution, and BR buffer solution as buffer solutions exhibited relatively low peak current and charge. However, the composite material with the PBS buffer solution showed the highest charge. Therefore, PBS buffer solution was selected as the supporting electrolyte.

[0061] The concentration of 2,4-diaminotoluene was fixed at 1.0 × 10⁻⁶. -3 mol / L, acrylic acid concentration is 4.0 × 10⁻⁶ -2 The charge of the 2,4-TDA-MIP / PDBSA / PANI / PANI composite material was investigated at different pH values ​​within the PBS buffer range of 5.91–7.17. As shown in Figures 3(a) and 3(b), the cyclic voltammetry curves of the composite material showed three pairs of distinct redox peaks in acidic solution, while only two pairs of distinct redox peaks appeared in alkaline solution. This may be because 2,4-dimethylaniline is more readily oxidized in acidic media. However, H... +Excessive concentration of 2,4-TDA leads to easier protonation and inhibits oxidation, resulting in a lower charge of the composite material. Therefore, the composite material exhibits the highest charge Q value at pH 6.81, and pH 6.91 is considered the optimal pH.

[0062] Optimization of the concentration ratio of template molecules to functional monomers in molecularly imprinted polymerization

[0063] The number of imprinted holes and their recombination ability with polymer monomers are affected by the concentration ratio of template molecules to functional monomers. Therefore, this influencing factor needs to be optimized. When the ratio is too small, the functional monomers and template molecules do not bind sufficiently, resulting in insufficient MIP stability; when the ratio is too large, too many non-specific imprinted holes are formed, which is not conducive to the recombination of MIP and polymer monomers. Under the condition of a multi-walled carbon nanotube concentration of 2.5 mg / mL, the effect of different concentration ratios of 2,4-diaminotoluene and acrylic acid on the charge and cyclic voltammetry curves of 2,4-TDA-MIP / PDBSA / PANI / PANI composite materials are shown in Figures 4(a) and 4(b). When the ratio is less than 1:4, the charge of the composite material gradually increases with the increase of the ratio, reaching the maximum at a ratio of 1:4; above 1:4, the charge decreases. Therefore, a ratio of 1:4 (5.0 × 10⁻⁶) is selected. -3 2.0×10 -2 The optimal concentration ratio of 2,4-diaminotoluene to acrylic acid is mol / L.

[0064] Optimization of scanning cycles and scanning potential in molecularly imprinted polymerization

[0065] The polymerization rate and film thickness of the polymer are closely related to the scanning potential range and the number of scan cycles. At a 2,4-TDA to acrylic acid concentration ratio of 1:4 (5.0 × 10⁻⁶), the polymerization rate and film thickness were... -3 2.0×10 -2 Under the condition of mol / L, the effects of different scanning potential ranges (-0.6-0.6V, -0.8-0.8V, -1.2-1.2V, -1.4-1.4V, -1.6-1.6V) and different scanning cycles (8, 12, 16, 20, 24) on the charge Q of the 2,4-DMA-MIP / PANI / NiHCF composite material were investigated. As shown in Figures 5(a) and 5(b), with the increase of the scanning potential range, the charge Q of the 2,4-DMA-MIP / PDBSA / PANI / PANI composite material first increased and then decreased, reaching its maximum in the range of -0.8 to 0.8V. A scanning potential range that is too narrow results in an excessively fast electron transfer rate, which is not conducive to the formation of the composite material; a range that is too wide reduces the polymer polymerization rate, increases the polymerization time on the electrode surface, and results in an uneven polymer film. Therefore, a scanning potential range of -1.2-1.2V was selected. The effects of different scanning cycles on the charge Q of the composite material were further compared. Figures 6(a) to 6(b) The study found that the composite material had the highest charge at 11 scan cycles. Too few scan cycles resulted in fewer imprinted holes in the polymer, a thinner film that was more prone to detachment, and reduced polymer repolymerization capacity, leading to a lower overall charge of the composite material. Exceeding 11 scan cycles resulted in a thicker polymer film, significantly hindering electron transfer in 2,4-TDA and increasing mass transfer resistance during elution. This made it difficult to hydrolyze the urethane bonds formed between 2,4-TDA and the functional monomers, further impeding elution. The unremoved template molecules occupied some of the imprinted holes, reducing the number of imprinted holes in the polymer and consequently lowering the charge of the composite material. Therefore, 11 scan cycles were chosen as the optimal number of scan cycles.

[0066] Optimization of scanning rate for molecularly imprinted polymerization

[0067] The scan rate during electrochemical polymerization also affects the thickness of the imprinted polymer film. A scan rate that is too slow results in a smooth, uniform, and thick polymer film. This greater thickness allows template molecules to be embedded within the polymer, making them difficult to wash out and reducing the number of imprinted voids. Conversely, a scan rate that is too fast results in a loose, rough, and porous film structure with insufficiently clear recognition sites on the film surface, thus reducing the specific recognition ability of the molecularly imprinted polymer. Therefore, under the conditions of 11 scan cycles and a scan potential of -1.2 to 1.2 V, the effects of scan rates of 0.05 V / s, 0.08 V / s, 0.10 V / s, 0.13 V / s, and 0.15 V / s on the charge Q were investigated. As can be seen from Figures 7(a) and 7(b), with the increase of scanning rate, the charge of the 2,4-TDA-MIP / PDBSA / PANI composite material shows a trend of first increasing and then decreasing. When the scanning rate is 0.08V / s, the charge Q value of the composite material is the largest. Therefore, 0.08V / s is selected as the optimal scanning rate.

[0068] The number of imprinted holes on the polymer is also affected by the elution time when eluting template molecules. Excessive elution time destroys the imprinted holes, affecting the polymer's three-dimensional network structure and reducing its stability. Conversely, insufficient elution time allows uneluted template molecules to occupy the imprinted holes, reducing their number and hindering further polymerization. The amino group in 2,4-TDA undergoes esterification with acrylic acid to form an urethane bond. Due to the decomposition of some H+ in the eluent (ethanol:ammonia = 20:1),... + During the urethane ester bond process, the carbonyl oxygen atom undergoes protonation, increasing the positive charge on the carbonyl carbon. This enhances the nucleophilic ability of the carbonyl oxygen atom to accept nucleophilic attacks, leading to water molecule attacking the carbonyl carbon and gradually hydrolyzing the urethane bond. This allows the template molecule 2,4-TDA to be successfully eluted. Figures 8(a) and 8(b) show that the composite material exhibits the highest charge at an elution time of 3 minutes. Therefore, the optimal elution time is 2 minutes.

[0069] 1) Constant current charge-discharge curve:

[0070] Figure 9 It is 2,4-TDA-MIP / PDBSA / PANI, 2,4-TDA-MIP / DBSA / PANI at 5A·g -1 The GCD curve at current density. From Figure 9 It can be seen that the discharge time of 2,4-TDA-MIP / PDBSA / PANI reaches 75.7s, while the discharge time of 2,4-TDA-MIP / PDBSA / PANI is slightly shorter, at 68.2s. According to the formula:

[0071]

[0072] The specific capacitance of the above four materials can be calculated, where C is the specific capacitance (F / g), Δt is the discharge time (s), I is the constant discharge current (A), m is the mass of the active material of the electrode material (g), and ΔV is the voltage drop during discharge (V).

[0073] Taking an average mass of 0.010 g of active material in the electrode materials, the specific capacitance of the two materials and PANI was calculated, and the results are shown in Table 1. Table 1 shows that 2,4-TDA-MIP / PDBSA / PANI has the highest specific capacitance, reaching 436.060 F / g, while 2,4-TDA-MIP / PDBSA / PANI has a slightly lower specific capacitance of 388.825 F / g. Both are higher than PANI, indicating that the imprinted polymer's specific recognition of aniline molecules leads to a higher degree of polymerization in the PANI molecular chain. Simultaneously, the imprinted holes in 2,4-TDA-MIP increase the specific surface area, thus enhancing the charge storage capacity of the composite material.

[0074] Table 1. Calculated specific capacitance data of the three materials and comparison results with PDBSA / PANIP and DBSA / PANI.

[0075]

[0076] Charge-discharge cycle test:

[0077] Depend on Figure 10 It can be seen that in 5A·g -1 After 5000 charge-discharge cycles under the specified conditions, 2,4-TDA-MIP / PDBSA / PANI retained approximately 90% of its capacity, indicating that the cycle stability of 2,4-TDA-MIP / PDBSA / PANI is improved compared to PDBSA / PANI.

Claims

1. A method for preparing ternary composite supercapacitor materials, characterized in that, The specific steps are as follows: Steps 1 and 2, Preparation of 4-TDA-MIP / MWCNT / PEC; Step 1 is implemented in the following steps: Using multi-walled carbon nanotubes (MWCNT / PEC) as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum electrode as the counter electrode, the electrode was placed in a phosphate buffer solution (PBS) containing 2,4-diaminotoluene, acrylic acid, and potassium dihydrogen phosphate. After continuous cyclic scanning and washing, the MWCNT-PEC electrode, which had undergone electrochemical reaction, was then ultrasonically eluted in an ethanol-ammonia solution to obtain the 2,4-diaminotoluene molecularly imprinted polymer / multi-walled carbon nanotube modified pencil lead electrode 2,4-TDA-MIP / MWCNT / PEC. In step 1, the effective electrode length of the multi-walled carbon nanotube (MWCNT / PEC) is 0.75-1.75 cm, and the concentration of 2,4-diaminotoluene is 1.0 × 10⁻⁶. - 3 -5.0×10 - 3 The concentration of acrylic acid is 5.0 × 10 mol / L. - 3 -2.0×10 - 2 mol / L, the pH of the PBS buffer is 5.91-7.17; Step 2: Preparation of molecularly imprinted polymer / polydodecylbenzenesulfonic acid modified electrode; Step 2 is implemented in the following steps: A traditional three-electrode system was used, with the 2,4-diaminotoluene molecularly imprinted polymer / multi-walled carbon nanotube modified pencil lead electrode 2,4-TDA-MIP / MWCNT / PEC obtained in step 1 as the working electrode, a calomel electrode as the reference electrode, and a platinum electrode as the counter electrode. The electrode was continuously cyclically scanned in a 0.05-0.15 mol / L dodecylbenzenesulfonic acid (DBSA) solution, and dried to obtain the 2,4-diaminotoluene molecularly imprinted polymer / polydodecylbenzenesulfonic acid / multi-walled carbon nanotube modified pencil lead electrode 2,4-TDA-MIP / PDBSA / MWCNT / PEC. Step 3, the preparation of 2,4-TDA-MIP / PDBSA / PANI, i.e., the ternary composite supercapacitor material; Step 3 is implemented in the following steps: In a mixed solution of H2SO4 and C6H5N as the supporting electrolyte, using the 2,4-diaminotoluene molecularly imprinted polymer / polydodecylbenzenesulfonic acid / multi-walled carbon nanotube modified pencil lead electrode 2,4-TDA-MIP / PDBSA / MWCNT / PEC obtained in step 2 as the working electrode, 2,4-diaminotoluene molecularly imprinted polymer / polydodecylbenzenesulfonic acid / polyaniline 2,4-TDA-MIP / PDBSA / PANI can be obtained after continuous scanning; In step 3, the concentration of H2SO4 in the mixed solution of H2SO4 and C6H5N is 0.2-0.8 mol / L, and the concentration of C6H5N is 0.05-0.3 mol / L.

2. The method for preparing the ternary composite supercapacitor material according to claim 1, characterized in that, In step 1, the device continuously cycles 11 times at a scanning rate of 0.08V / s within a potential range of -1.2 to 1.2V. The device is cleaned several times with double-distilled water. The volume ratio of ethanol to ammonia in the ethanol-ammonia solution is 10:1 to 20:

1. The ultrasonic elution time is 1 to 5 minutes.

3. The method for preparing the ternary composite supercapacitor material according to claim 1, characterized in that, In step 2, the scanning rate is 0.05-0.15 V / s, the potential range is -0.2-0.6V, and the continuous cyclic scanning is performed for 6-14 cycles.

4. The method for preparing the ternary composite supercapacitor material according to claim 1, characterized in that, In step 3, the scanning potential range is -0.2 to 1.85 V, the scanning rate is 0.03 to 0.15 V / s, and the scanning is continuous for 6 to 14 cycles.

Citation Information

Patent Citations

  • Preparation and test method of electromagnetic composite material

    CN110470710A